2013
DOI: 10.1152/ajprenal.00056.2013
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomal Wilms' tumor-1 as a potential biomarker for podocyte injury

Abstract: Renal Wilms' tumor-1 (WT-1) staining is used to detect podocyte loss in kidney biopsies. We aimed to determine if urinary exosomal WT-1 could serve as a noninvasive biomarker of podocyte injury. We examined WT-1 by Western blot in a human podocyte-like cell line, a mouse model of podocyte injury, and human subjects with podocyte disorders. WT-1 was detected in exosomal fraction of the conditioned media from podocytes and increased 48 h after hTGF-β1 stimulation. Cellular WT-1 decreased in podocytes following h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 25 publications
2
95
1
1
Order By: Relevance
“…Several markers of podocyte damage have been identified in uEVs, including podocalyxin, podoplanin, 83 and WT-1. 80,81 A protective role of EVs derived from MSCs has been described in models of kidney damage. It is suggested that these EVs from MSCs are involved in transfer of mRNA, miRNA, and proteins and reprogramming of their phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several markers of podocyte damage have been identified in uEVs, including podocalyxin, podoplanin, 83 and WT-1. 80,81 A protective role of EVs derived from MSCs has been described in models of kidney damage. It is suggested that these EVs from MSCs are involved in transfer of mRNA, miRNA, and proteins and reprogramming of their phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In FSGS, 80 a disease with significant podocyte damage, Wilm's tumor-1 (WT-1), a transcription factor required for kidney development, was examined in uEXs as a marker for podocytes damage. Increased expression of WT-1 in uEXs was found 1 week earlier than urinary albumin excretion in a mouse model of collapsing glomerulopathy.…”
Section: Glomerular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The identification of biomarkers specific for the FSGS disease state may also provide insights into the pathomechanism of FSGS. Although increasing efforts have been made to identify such biomarkers, few novel noninvasive biomarkers have yet been identified (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…The renal tissues were then washed with PBS and fixed with 1% osmium tetroxide. After dehydration in an acetone gradient and embedment with Araldite M (Sigma-Aldrich), the tissues were stained with uranyl acetate and lead citrate (10). The microstructures were detected under a Philips 301 electron microscope.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%